Prothrombin Is Responsible for the Lupus Cofactor Phenomenon in a Patient with Lupus Anticoagulant/Hypoprothrombinemia Syndrome - Pengo, Vittorio; Zardo, Lorena; Cattini, Maria Grazia; Bison, Elisa; Pontara, Elena; Altinier, Sara; Cheng, Chunyan; Denas, Gentian (TH Open, 2020)
Lupus anticoagulant is a misnomer as it is commonly associated with thromboembolic events. In few cases, the name retains its literal meaning when it characterizes patients with a bleeding disorder. We describe a patient with lupus anticoagulant, hypoprothrombinemia, and major bleeding (lupus anticoagulant/hypoprothrombinemia syndrome). Immunological studies revealed a huge amount of circulating monoclonal immunoglobulin M lambda (IgMλ) antiphosphatidylserine/prothrombin antibodies (14,400 U/mL). Affinity purified monoclonal antibodies (440 U/mL) prolonged the coagulation time of normal plasma by 12.2 seconds (diluted Russell viper venom time) and 25.5 seconds (silica clotting time). The original patient's plasma mixed 1:1 with normal plasma showed a marked prolongation of coagulation times (lupus cofactor) from a ratio of 2.94 to 5.23 in diluted Russel viper venom time and from 2.30 to 3.00 using the silica clotting time. Human prothrombin added to original patient's plasma caused a marked prolongation of coagulation times in diluted Russell viper venom test thus unequivocally explaining the lupus cofactor phenomenon. In conclusion, we have shown that lupus anticoagulant/hypoprothrombinemia syndrome is attributable to monoclonal IgMλ antibodies directed to phosphatidylserine/prothrombin and that prothrombin is the protein responsible for the observed lupus cofactor phenomenon.
Keywords: antiphospholipid antibodies; lupus coagulation inhibitor; prothrombin